Complexity, Uncertainty and Change in News Organizations. Issue 2 (3rd April 2019) - Wilczek, Bartosz
ABSTRACT: Media managers and journalists have responded to digitalization over time by implementing online journalism and by converging and de-converging print and online newsrooms. Drawing on complexity and uncertainty theories, this article develops a cycle model, which furthers the understanding of why and how news organizations change. Qualitative and quantitative findings in two European legacy media companies indicate that managers are constantly striving to minimize their own complexity and uncertainty, which, in turn, drives change in news organizations through different stages that are characterized by economization and integration or investment and specialization. More specifically, under lower external and internal complexity and uncertainty, managers are pushing news organizations toward more economization and integration. However, they invest and specialize if either their external or their internal complexity and uncertainty increase. Moreover, the findings reveal the mechanism through which the internal complexity and uncertainty arise, and they show differences depending on the ownership structure of a news organization.